Improving the Psychological Well-Being of Social Media Users Through Group Counseling Services Using Stress Inoculation Techniques on Students - Dlt, Hapni Madini; Nasution, Fauziah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to determine the effectiveness of group guidance services using the Stress Inoculation Training (SIT) technique in enhancing the psychological well-being of social media users at Budisatrya High School Medan. The research adopts a quantitative approach with a one-group pre-test - post-test design to evaluate changes before and after the intervention. The participants consisted of eight students identified with varying levels of psychological well-being, as assessed through an initial screening process. The intervention was conducted through a series of structured group counseling sessions integrating SIT phases: conceptual education, skills acquisition, and application. The statistical analysis revealed a significant improvement in psychological well-being, with the average score increasing from 91.00 (pretest) to 107.63 (post-test). The normality test indicated that the post-test data were normally distributed, while the pretest data were not. The homogeneity of variance was confirmed with a significance value of 0.533, allowing the use of parametric tests. The paired sample t-test yielded a value of t = -13.749 and Sig. = 0.000, indicating a statistically significant difference between the pre-test and post-test scores. These findings suggest that group guidance services incorporating SIT are effective in improving students’ psychological well-being, particularly in managing stress related to excessive social media use. The study underscores the importance of integrating psychological resilience training into school-based mental health programs to address the growing psychosocial challenges in the digital era.